Sensitivity of Iodine-Mediated Stratospheric Ozone Loss Chemistry to Future Chemistry-Climate Scenarios - Klobas, J. Eric; Hansen, Janina; Weisenstein, Debra K.; Kennedy, Robert P.; Wilmouth, David M. (Frontiers in Earth Science, 2021)
As the chemical and physical state of the stratosphere evolves, so too will the rates of important ozone-destroying reactions. In this work, we evaluate the chemistry-climate sensitivity of reactions of stratospheric iodine, reporting the iodine alpha factor (the efficiency of ozone loss mediated by a single iodine atom relative to the ozone loss mediated by a single chlorine atom) and the iodine eta factor (the efficiency of ozone loss mediated by a single iodine atom relative to the ozone loss mediated by a single chlorine atom in a benchmark chemistry-climate state) as a function of future greenhouse gas emissions scenario. We find that iodine-mediated ozone loss is much less sensitive to future changes in the state of the stratosphere than chlorine- and bromine-mediated reactions. Additionally, we demonstrate that the inclusion of the heterogeneous reaction of ozone with aqueous iodide in stratospheric aerosol produces substantial enhancements in the iodine alpha and eta factors relative to evaluations that consider gas-phase iodine reactions only. We conclude that the share of halogen-induced ozone loss due to reactions of iodine will likely be greater in the future stratosphere than it is today.